Praktik Komunikasi Inklusif Influencer Disabilitas di Instagram: Studi Kasus Akun @Jenniferrnatalie - Susilawaty, Fera Tri; Halika, La Ode Herman; Wardanhi, Sartika Sari (Warta Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - This study aims to analyze the practice of inclusive communication by a disabled Indonesian influencer through a case study of the Instagram account @jenniferrnatalie. Theories of inclusive communication, media representation, and digital activism were used as the theoretical framework to explain how social media functions as a participatory space for people with disabilities, especially the Deaf community. This research employed a qualitative descriptive approach with a case study method, analyzing 18 content posts published from November 2024 to April 2025. The findings reveal that Jennifer Natalie consistently uses accessibility features such as sign language, captions, and inclusive visuals in her content. Advocacy and educational narratives emerged as the dominant themes, delivered in a personal and relatable style. Audience responses were generally positive, with high engagement particularly seen in content related to family and personal experiences. These findings indicate that social media can serve as an effective medium for inclusive communication and as a platform for empowerment and self-representation of people with disabilities. This study underscores the importance of accessibility- and inclusivity-based communication strategies in raising awareness and challenging stereotypes about disability.Keywords: Accessibility; Disability; Inclusive Communication; Influencer; Instagram Abstrak - Penelitian ini bertujuan untuk menganalisis praktik komunikasi inklusif oleh influencer disabilitas Indonesia melalui studi kasus akun Instagram @jenniferrnatalie. Teori komunikasi inklusif, representasi media, dan aktivisme digital digunakan sebagai landasan teoritis untuk menjelaskan bagaimana media sosial menjadi ruang partisipatif bagi penyandang disabilitas, khususnya komunitas Tuli. Penelitian menggunakan pendekatan deskriptif kualitatif dengan metode studi kasus, menganalisis 18 konten yang dipublikasikan antara November 2024 hingga April 2025. Hasil penelitian menunjukkan bahwa Jennifer Natalie secara konsisten menggunakan simbol aksesibilitas seperti bahasa isyarat, caption, dan visual inklusif dalam kontennya. Narasi advokasi dan edukasi menjadi tema dominan, dengan pendekatan yang personal dan representatif. Respons audiens terhadap konten tersebut umumnya positif dan menunjukkan interaksi yang cukup aktif, terutama pada konten bertema keluarga dan pengalaman pribadi. Temuan ini mengindikasikan bahwa media sosial dapat berfungsi sebagai medium komunikasi inklusif yang efektif serta ruang pemberdayaan dan representasi diri penyandang disabilitas. Studi ini memperkuat pentingnya strategi komunikasi yang berbasis aksesibilitas dan inklusivitas dalam membangun kesadaran serta mendobrak stereotip tentang disabilitas.Kata kunci: Aksesibilitas; Disabilitas; Influencer; Instagram; Komunikasi Inklusif